Evaluating cardiac performance in beagle dogs: Transesophageal echocardiography and myocardial work assessment - Beibei Ge; Changqing Miao; Di Xu; Mingxia Li; Fang Xu; Xiaoxian Wang; Fen Chen; Yan Li; Yan Chen; Chanjuan Gong; Peng Li; Fang Wang; et al. (Heliyon, 2025)
Objectives: This study aimed to establish standard transesophageal echocardiographic (TEE) measurements of left ventricular (LV) morphology, function, and myocardial work parameters in healthy Beagle dogs using pressure-strain loops (PSL). Additionally, it sought to standardize optimal TEE imaging techniques and explore the potiential application of myocardial work analyis in veterinary medicine. Methods: Thirty-seven healthy male Beagle dogs were anesthetized, intubated, and mechanically ventilated for TEE examinations. LV systolic and diastolic function were evaluated, with simultaneous invasive femoral artery pressure measurements. Left ventricular global longitudinal strain (GLS), myocardial work parameters, PSL-derived metrics were analyzed. Results: The mean LV GLS was −16.0 ± 4.0 %, and the LV global myocardial work index (GWI) was 888 ± 298.6 mmHg∗%. Global Myocardial work efficiency (GWE) was 88 ± 3 %, while global myocardial wasted work (GWW) was 152 mmHg∗% (38–431 mmHg∗%). LV ejection fraction (LVEF) averaged 58.7 ± 4.4 %. Left ventricular end-diastolic (LVEDV) and end-systolic volume (LVESV) were 19.3 ± 5.2 ml and 8.0 ± 2.3 ml, respectively. Regional myocardial work analysis revealed significant differences between the interventricular septum and lateral wall. The lateral wall demonstrated reduced segmental work efficiency (SWE), work index (SWI), and constructive work (SCW) but higher wasted work (SWW) compared to the septum (p < 0.05). Conclusions: TEE provides detail morphological and functional assessments of the Beagle hearts, offering reference data for future studies. Myocardial work analysis presents a novel method for evaluate myocardial contractility and mechanical properties, with promising applicatons in veterinary medicine.